Relación entre el consumo de agua cruda y la incidencia de enfermedades en ganado aviar en la granja avícola “Zambrano Ponce” - Zambrano Ponce, Nixon Javier (2019)
The research consisted in evaluating the relationship between the consumption of raw water and the incidence of diseases in avian livestock of a poultry farm. This was validated through the experimental method, observation techniques and laboratory analysis. Three stages were addressed: 1) Application of a simple DCA for the production of chickens with different types of water (purified, underground and surface). 2) Determination of the incidence of diseases in avian livestock; Once the experiment was completed, necropsy analysis was performed on the experimental units to identify the appearance of diseases and was evaluated with a binary logistic regression. 3) Establishment of a water treatment alternative for supplying the poultry farm; calculations were made for the sizing of equipment that would improve the quality of the water in the area to hydrate the poultry, among which we can include sand trap and filtration system. It was obtained as a result that the parameters of pH, total solids, fecal and total coliforms are within the permissible limits established in the TULSMA for livestock use, unlike dissolved oxygen. It was also found that the types of water in the treatment do not generate significant differences in the weight of the avian livestock. But there is significance (p <0.05) between the type of water and the appearance of five diseases. It is concluded that the type of water used in the experiment influenced the appearance of most avian diseases, excluding ascites.